2009
DOI: 10.1159/000209285
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Myelomeningocele Carried Out at ‘Time Zero’ Immediately after Birth

Abstract: Background/Aims: To present a protocol of immediate surgical repair of myelomeningocele (MMC) after birth (‘time zero’) and compare this surgical outcome with the surgery performed after the newborn’s admission to the nursery before the operation. Methods: Data from the medical files of 31 patients with MMC that underwent surgery after birth and after admission at the nursery (group I) were compared with a group of 23 patients with MMC admitted and prospectively followed, who underwent surgery immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
2
22
1
3
Order By: Relevance
“…Investigation of proposed type of delivery revealed high rates (25%) of vaginal delivery. The study suggested that women undergoing transvaginal delivery may receive irregular prenatal care that would consequently lead to the failure of diagnosing MM in the fetus, which in turn may lead to misguided management based on the type of delivery.Vaginal delivery may increase the risk of rupture and infection of MM during the passage of the fetus from the birth canal; however, indication of cesarean delivery in these pregnant women and its benefits in newborn are still controversial 12,24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Investigation of proposed type of delivery revealed high rates (25%) of vaginal delivery. The study suggested that women undergoing transvaginal delivery may receive irregular prenatal care that would consequently lead to the failure of diagnosing MM in the fetus, which in turn may lead to misguided management based on the type of delivery.Vaginal delivery may increase the risk of rupture and infection of MM during the passage of the fetus from the birth canal; however, indication of cesarean delivery in these pregnant women and its benefits in newborn are still controversial 12,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of an obstetric department in our hospital, these children usually arrive at our hospital 24 h after birth. This delays the immediate closure of the lesions, which should in fact be corrected immediately 12 , and hinders the training of a multidisciplinary team involved in intrauterine closure and correction of MM 1 . The same situation is observed in other Brazilian states where many maternity hospitals do not have a unit for pediatric neurosurgery, thus making it necessary to transfer these children to other hospitals 22,26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations